Epidural analgesia in labor: ethical considerations - Messina, Marianna; Pala, Franco (Medicina e Morale, 1993)
The physiopatological, psychological and sociological presuppositions of labor pains are taken into consideration in order to analyse the role of the introduction of analgesie techniques with particular reference to epidural analgesia. Since there is an increasing use of medicai techniques and the risk of the woman avoiding her responsibilities, epidural analgesia can allow the woman to experience her labor better when the strong pain becomes a reason for anguish and stress for the mother and a danger for the health of the fetus because of the vicious circle that stress provokes. Even in normal labor, if the woman requests it, this analgesia seems to be a useful instrument for her in that it allows her to experience an unique event with greater serenity. One hopes that the abolition of pain will be considered a means and not an end and that the whole team (obstetrician, midwife, anesthetist, pediatrician), will collaborate with the mother both before, and with adeguate preparation, also during labor, so that the woman can freely and responsibly manage the birth of her child.